The paradox of dissent: judicial dissent and the projects of international criminal justice - Mistry, Hemi (Oxford University Press, 2015)
Additional opinions — dissenting opinions, separate opinions, declarations, and permutations thereof — are a familiar, if sometimes controversial, aspect of the international jurisprudential landscape. Given that the controversy provoked by additional opinions focuses on their perceived impact on the authority of judgments and decisions of international tribunals, and even the authority of the institutions themselves, additional opinions go to the heart of the manner in, and effectiveness by, which international tribunals discharge their functions. Yet, particularly in the context of international criminal justice, additional opinions have often been overlooked as a subject of critical engagement in their own right. Therefore, the purpose of this article is bring into focus the practice of judicial dissent, that is, the expression of strongly held and fundamental disagreement by judges through the vehicle of the additional opinion, and to stimulate a wider critical engagement with dissentient judicial practice. Rather than providing a review of the orthodox and doctrinal arguments in favour and against the publication of additional opinions, this article offers a reading of five prominent examples of judicial dissent in international criminal law and suggests how this practice could be conceived from the perspective of the functions that international criminal adjudication is expected to serve.